1995
DOI: 10.1159/000120972
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Involution of an Intra-Axial Brain Stem Lesion: A Case Report

Abstract: This report describes the spontaneous involution of an intrinsic brain stem lesion whose clinical and MRI characteristics strongly suggest a tumor etiology. Nonoperative experiences with central nervous system tumors have shown that they may sometimes exhibit prolonged periods of dormancy. There are several reports of ‘disappearing’ CT lesions which have all been inflammatory, infective, or immunological. No histologically proven tumor has been shown to spontaneously involute, nor have ‘disappearing’ lesions b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Schmandt, et al, 44 reviewed 22 patients in whom regression of astrocytomas was demonstrated. In this review, 20 of the lesions were in the hypothalamic-chiasmatic region and two were in the brainstem with a pontine epicenter (the cases reported by Rao 40 and Lenard 29 and their colleagues). Patients ranged in age from 5 months to 8 years at the time of presentation.…”
Section: Spontaneous Regression Of Brainstem Lesionsmentioning
confidence: 95%
See 1 more Smart Citation
“…Schmandt, et al, 44 reviewed 22 patients in whom regression of astrocytomas was demonstrated. In this review, 20 of the lesions were in the hypothalamic-chiasmatic region and two were in the brainstem with a pontine epicenter (the cases reported by Rao 40 and Lenard 29 and their colleagues). Patients ranged in age from 5 months to 8 years at the time of presentation.…”
Section: Spontaneous Regression Of Brainstem Lesionsmentioning
confidence: 95%
“…Rao, et al, 40 reported on a 4-year-old child who presented with a 9-month history of diplopia, facial asymmetry, and unsteadiness. On examination the patient was found to suffer from sixth and seventh cranial nerve palsies, nystagmus, and pyramidal and dysmetric signs.…”
Section: Spontaneous Regression Of Brainstem Lesionsmentioning
confidence: 99%
“…Two additional cases suggest spontaneous regressions of juvenile pilocytic astrocytomas of the visual pathways due to tumor absence at autopsy years after a partial resection and a biopsy [1]. Four of the 22 cases had a documented increase in tumor size prior to the regression [4, 5, 6]and 3 had a history suggestive of tumor progression before diagnosis [7, 8, 9]. 12 cases had NF1.…”
Section: Discussionmentioning
confidence: 99%
“…As seen in our case, despite tumor regression, clinical symptoms do not necessarily improve. Only 3 of the 22 patients reviewed had clear-cut clinical improvement [7, 9, 12]. Three had normal clinical examinations even prior to the regression and despite their tumor [5, 6].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, spontaneous regression of presumed diffuse brainstem gliomas in younger children, including a neonate, has been reported. [14][15][16] Hence, any atypical clinical and neuroimaging features, such as the congenital presentation in our 2 cases, must be considered cautiously in the diagnosis and management of presumed DIPG.…”
Section: Casementioning
confidence: 96%